The Influence of Government Ownership, Institutional Ownership, Foreign Ownership and Environmental Performance on Carbon Emission Disclosure With The Moderation Variable of Financial Distress - Endah Sri Sri Wahyuni; Revan Mairjal; Imam Prayogo; Sulastini Sulastini; Adhi Surya; Syahrial Shaddiq; Muhammad Bahit (Postgraduate Program Merdeka University, 2025)
Corporate social responsibility and interest in environmental impacts can influence a company's environmental policies and practices, including the distribution of emissions. This research aims to analyze and test the influence of government ownership, institutional ownership, foreign ownership and environmental performance on carbon emissions disclosure with the moderating variable financial distress in energy sector companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The type of research used is associative quantitative with a sample of 45 companies from a population of 76 energy sector companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The analysis technique used in this research is moderated regression analysis with a significance level of 5%. The results of this study show that ownership and institutional ownership partially have no effect on carbon emissions coverage, foreign ownership and environmental performance partially influence carbon emissions coverage, financial difficulties can moderate ownership on carbon emissions coverage, and financial difficulties cannot moderate institutions. ownership, device ownership and environmental performance on carbon emissions JEL Classification: G10, F64 DOI: https://doi.org/10.26905/afr.v8i1.13803